A phase 2b randomized, controlled trial of the efficacy of the GMZ2 malaria vaccine in African children. Issue 38 (31st August 2016) - ,; Ouédraogo, Alphonse; Kargougou, Désiré; Nébié, Issa; Débé, Siaka; Diarra, Amidou; Bougouma, Edith; Hounkpatin, Aurore B.; Adegnika, Ayola Akim; Lell, Bertrand; Joanny, Fanny; Honkpehedji, Yabo Josiane; et al.
Highlights: The GMZ2 fusion protein consist of the non-repeat region of falciparum GLURP genetically fused to a msp3 fragment. The GMZ2 fusion protein elicited functional antibodies in phase 1 studies. In the ATP analysis, vaccine efficacy adjusted for age and site was 14% (95% CI: 3.6%, 23%). Vaccine efficacy was higher in older children. In GMZ2-vaccinated children, the incidence of malaria decreased with increasing vaccine-induced anti-GMZ2 IgG concentration. Abstract: Background: GMZ2 is a recombinant protein malaria vaccine, comprising two blood-stage antigens of Plasmodium falciparum, glutamate-rich protein and merozoite surface protein 3. We assessed efficacy of GMZ2 in children in Burkina Faso, Gabon, Ghana and Uganda. Methods: Children 12–60 months old were randomized to receive three injections of either 100 μg GMZ2 adjuvanted with aluminum hydroxide or a control vaccine (rabies) four weeks apart and were followed up for six months to measure the incidence of malaria defined as fever or history of fever and a parasite density ⩾5000/μL. Results: A cohort of 1849 children were randomized, 1735 received three doses of vaccine (868 GMZ2, 867 control-vaccine). There were 641 malaria episodes in the GMZ2/Alum group and 720 in the control group. In the ATP analysis, vaccine efficacy (VE), adjusted for age and site was 14% (95% confidence interval [CI]: 3.6%, 23%, p -value = 0.009). In the ITT analysis, age-adjusted VE was 11.3% (95% CI 2.5%, 19%, p -value = 0.013). VE was higher in older children. In GMZ2-vaccinated children, the incidence of malaria decreased with increasing vaccine-induced anti-GMZ2 IgG concentration. There were 32 cases of severe malaria (18 in the rabies vaccine group and 14 in the GMZ2 group), VE 27% (95% CI −44%, 63%). Conclusions: GMZ2 is the first blood-stage malaria vaccine to be evaluated in a large multicenter trial. GMZ2 was well tolerated and immunogenic, and reduced the incidence of malaria, but efficacy would need to be substantially improved, using a more immunogenic formulation, for the vaccine to have a public health role.